Molecular characterization of glucose-6-phosphate dehydrogenase deficiency in Jeddah, Kingdom of Saudi Arabia - Al-Jaouni, Soad K (BioMed Central, 2011)
BACKGROUND: The development of polymerase chain reaction (PCR)-based methods for the detection of known mutations has facilitated detecting specific red blood cell (RBC) enzyme deficiencies. We carried out a study on glucose-6-phosphate dehydrogenase (G6PD) deficient subjects in Jeddah to evaluate the molecular characteristics of this enzyme deficiency and the frequency of nucleotide1311 and IVS-XI-93 polymorphisms in the glucose-6-phosphate dehydrogenase gene. RESULTS: A total of 1584 unrelated Saudis (984 neonates and 600 adults) were screened for glucose-6-phosphate dehydrogenase deficiency. The prevalence of glucose-6-phosphate dehydrogenase deficiency was 6.9% (n = 110). G6PD Mediterranean mutation was observed in 98 (89.1%) cases, G6PD Aures in 11 (10.0%) cases, and G6PD Chatham in 1 (0.9%) case. None of the samples showed G6PD A‾ mutation. Samples from 29 deficient subjects (25 males and 4 females) were examined for polymorphism. The association of two polymorphisms of exon/intron 11 (c.1311T/IVS-XI-93C) was observed in 14 (42.4%) of 33 chromosomes studied. This association was found in 9 (31.0%) carriers of G6PD Mediterranean and in 4 (13.8%) carriers of G6PD Aures. CONCLUSIONS: The majority of mutations were G6PD Mediterranean, followed by G6PD Aures and < 1% G6PD Chatham. We conclude that 1311T is a frequent polymorphism in subjects with G6PD Mediterranean and Aures variants in Jeddah.